2020
DOI: 10.1108/jpbm-02-2019-2262
|View full text |Cite
|
Sign up to set email alerts
|

From fandom to fad: are millennials really engaged with and loyal to their loved brands on social media?

Abstract: Purpose Exerting a peculiar fascination on both managers and academics, Millennials can be distinguished from other cohorts by their intense exposure to the internet and heavy use of social media, which, in turn, affect their identity formation, brand engagement, loyalty and purchase behaviour. Yet, uncertainties regarding online engagement and the real benefits brands can reap from Millennials’ avid use of social media remain. Therefore, by developing a holistic model of drivers and outcomes, this study aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 102 publications
(156 reference statements)
3
23
0
4
Order By: Relevance
“…However, the study results showed that online engagement was not a significant predictor of brand loyalty. A similar finding was noted in recent research, which studied the relationship between brand love, social media engagement and brand loyalty among millennials (Fernandes and Inverneiro, 2020). The disconnect between online engagement and brand loyalty may be related to the fact that although baby boomers may establish a parasocial relationship with hospitality brands, they do not actively engage with them in social media, leading to a nonsignificant relationship with brand loyalty.…”
Section: Results Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…However, the study results showed that online engagement was not a significant predictor of brand loyalty. A similar finding was noted in recent research, which studied the relationship between brand love, social media engagement and brand loyalty among millennials (Fernandes and Inverneiro, 2020). The disconnect between online engagement and brand loyalty may be related to the fact that although baby boomers may establish a parasocial relationship with hospitality brands, they do not actively engage with them in social media, leading to a nonsignificant relationship with brand loyalty.…”
Section: Results Discussionsupporting
confidence: 83%
“…The lack of research on the older generation is an important gap, considering the significant business value of these consumers for the hospitality industry. In addition, generational theory suggests that different cohorts may have distinct consumption attitudes and behaviors given their varying formative experiences, values and technology usage (Fernandes and Inverneiro, 2020). There are some indications that baby boomers vary from other generations in their engagement motivation and brand attitude on social media (Krishen et al, 2016).…”
Section: Ijchm 335mentioning
confidence: 99%
See 1 more Smart Citation
“…In the concrete case, this means that the more passionate the Erasmus students felt about their host country, the more likely they were to post pictures on their social media accounts and to share their experiences with Erasmus on the internet. Interestingly, recent research has found that, although some consumers love brands, they do not actively engage with them on social media (Fernandes and Inverneiro, 2020). This may explain why eWOM was one of the weakest outcomes for destination brand love in this study.…”
Section: Assessment Of the Structural Model Resultsmentioning
confidence: 62%
“…Bergkvist and Bech-Larsen (2010) stress the importance of the identification with the brand, as the closer the consumer self-image is to the brand image, the higher is the level of identification with the brand. Fernandes and Inverneiro (2020) reiterate the connection between brand identification and brand love. Carroll and Ahuvia (2006) also mention self-expression as an antecedent of brand love, as consumers value "the degree to which the specific brand enhances one's social self and/or reflects one's inner self" (p. 82), and thus prefer brands that help create and reinforce their identities and its expression.…”
Section: Antecedents and Consequences Of Brand Lovementioning
confidence: 99%